Construction and Validation of the Scale for the Study of Cyberbullying (SSC) - Zdzisław Bartkowicz; Andrzej Chudnicki; Natalia Kamila Czopek (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: Cyberbullying is becoming an increasingly serious problem among children and adolescents, threatening safety and mental health, and posing new tasks for psychological and pedagogical support. Diagnosing the dangers of engaging in cyberbullying is a task that requires appropriate tools to assess in detail the ways in which others are attacked virtually and the individual's participation as a perpetrator or victim of cyberbullying. It is felt that there is a lack of appropriate tools that measure cyberbullying multifacetedly, as a way of behaving in the virtual world that is perceived by the individual in terms of good and bad. Research Aim: This article presents the conceptual assumptions and stages in the construction of a new tool to measure cyberbullying. The Cyberbullying Screening Scale consists of 4 subscales measuring the frequency of manifesting and experiencing 17 modes of virtual harm. In addition, respondents rated how often individual acts of cyberbullying occur in the school environment and to what extent they are bad or meaningless. Method: The analysis of psychometric properties was based on the results of the survey of 240 secondary school students. Results: Factor analysis established a set of items for the individual subscales. High reliability indices were obtained for all subscales. A preliminary standardisation of the tool was carried out, as a result of which it was determined how many perpetrators, victims and aggressive victims of cyberbullying are in the study group. Conclusion: The results obtained are consistent with those obtained in different countries using other tools.